Respuesta :

Correct Question

Lauren simplified the expression [tex](m^{-7} )^{-5}[/tex]

as shown

[tex](m^{-7} )^{-5} = m^{-7+(-5)} = m^{-12} = \frac{1}{m^{12} }[/tex]

Which statement explains Lauren's error

Answer:

  • She should have multiplied the exponents instead of adding them

Step-by-step explanation:

The error in her workings is that she added the exponent instead of multiplying them

According to the law of indices

[tex](x^{a})^{b} = x^{ab}[/tex]

From the above illustration, it'll be observed that the exponents a and b were multiplied instead of adding or subtracting

Same thing is applicable to this expression in Lauren's case

She ought to multiply -7 and -5 to give 35 not adding them to give -12

The right solution to the expression is as follows:

[tex](m^{-7} )^{-5} = m^{(-7)(-5)}[/tex]

[tex](m^{-7} )^{-5} = m^{(-7*-5)}[/tex]

[tex](m^{-7} )^{-5} = m^{35}[/tex]

ACCESS MORE
EDU ACCESS
Universidad de Mexico